The Development of an In Vitro Horizontal Diffusion Cell to Monitor Nasal Powder Penetration Inline - Péter Gieszinger; Tamás Kiss; Piroska Szabó-Révész; Rita Ambrus (MDPI AG, 2021)
The development of in vitro investigation models could be important using sensitive and fast methods during formulation. Intranasal applied drugs (meloxicam, lamotrigine, and levodopa) avoid the gastrointestinal tract and can achieve higher bioavailability, therefore a penetration extent is a key property. In this study, the in vitro adaptability of a modified horizontal diffusion cell was tested by using these model active pharmaceutical ingredients (APIs). The special factors consisted of the volume of the chambers, the arrangement of the stirrers, the design of probe input for real-time analysis and decreased membrane area. Membranes were impregnated by isopropyl myristate and by using phosphate buffer to evaluate the effect of API hydrophilicity on the diffusion properties. The lipophilicity of the API was proportional to the penetration extent through isopropyl myristate-impregnated membranes compared with buffer-soaked membranes. After evaluating the arithmetic mean of standard relative deviations and the penetrated extent of APIs at 15 min, Metricel® could be suggested for levodopa and meloxicam, and Whatman™ for lamotrigine. The modified model is suitable for inline, real-time detection, at nasal conditions, using small volumes of phases, impregnated membrane, to monitor the diffusion of the drug and to determine its concentration in the acceptor and donor phases.